2020
DOI: 10.29271/jcpsp.2020.10.1047
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Operated T3-T4 Gastric Cancer

Abstract: Objective: To investigate the prognostic factors affecting survival in patients with a deep gastric wall invasion of T3-T4 advanced gastric cancer. Study Design: Descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The first surgical procedure in TLDG is to resect the distal stomach and perigastric lymph nodes radically, which accounts for primary intraoperative bleeding and embodies the oncological safety of the surgery [ 11 ]. In the present study, this procedure in the B-IIB and R-Y groups is almost identical and performed in a standardized way, which could explain the results that the number of retrieved lymph nodes and intraoperative bleeding did not differ between the study groups.…”
Section: Discussionmentioning
confidence: 99%
“…The first surgical procedure in TLDG is to resect the distal stomach and perigastric lymph nodes radically, which accounts for primary intraoperative bleeding and embodies the oncological safety of the surgery [ 11 ]. In the present study, this procedure in the B-IIB and R-Y groups is almost identical and performed in a standardized way, which could explain the results that the number of retrieved lymph nodes and intraoperative bleeding did not differ between the study groups.…”
Section: Discussionmentioning
confidence: 99%
“…GC is divided into early GC (stage I and II) and advanced GC (stage III or higher tumors) ( 36 38 ), and there are differences in treatment and surgical methods between early and advanced GC ( 39 , 40 ). Uzun et al ( 41 ) revealed that T1-T2 and T3-T4 classifications of patients with GC showed differences in their clinicopathological characteristics and survival status. T3-T4 classification was an important indicator for patients with GC to choose GC chemotherapy and surgical procedures ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the American Joint Committee on Cancer Staging System (8 th edition) ( 31 ), and the differences in treatment and surgical methods between early gastric cancer group (stage I and II) and advanced gastric cancer group (stage III or higher tumors) ( 36 40 ), patients with GC with regards to pathological stage were divided into the early GC group (stage I and II) and advanced GC group (stage III or higher tumors). According to the United States Joint Committee on Cancer Staging System (8 th edition) ( 31 ) and the differences between T3-T4 group and T1-T2 classification group with GC in chemotherapy and surgery ( 41 43 ), patients with GC in tumor (T) classification were divided into the T1-T2 and T3-T4 groups.…”
Section: Methodsmentioning
confidence: 99%